Global Market Entry Strategies in K-Pop’s Expansion into Southeast Asia A Comparative Study on SM Entertainment, YG Entertainment, JYP Entertainment, & HYBE - Adiasri Putri Purbantina; Anugrah Nurul Hidayati; Ayunda Roliana Dewi; Khalista Noor; Reisa Najma Salsabila (Jurnal Sentris, 2025)
South Korea's leading K-Pop multinational corporations—HYBE, SM, JYP, and YG—have actively pursued international growth, with Southeast Asia emerging as a pivotal market. This research investigates the strategic approaches these companies employ to penetrate the Southeast Asian market, a region characterized by substantial K-pop fandom. Utilizing a qualitative case study design, the analysis draws upon secondary data, including news reports and official corporate publications, to examine the Big Four's global market entry models through several categories, including exports, licensing, alliances or joint ventures, and FDI. The study finds that the Big Four primarily focus on exporting K-pop products to Southeast Asia, capitalizing on its large, loyal fan base. These companies prefer partnership and distribution strategies to enter the Southeast Asian market while reducing risk by avoiding long-term investment through FDI (i.e., establishing subsidiaries, acquiring local companies, or building new business operations in the region).Keywords: market entry strategy, big four agencies, Korean music industry, Southeast Asia.